Korelasi Minat, Motivasi dan Hasil Belajar melalui Pembelajaran Berdiferensiasi - A, Komarudin; Hakim, Shofi Al; Nursafaat, Abdul Kholik (Universitas Islam Jember, 2024)
Interest is a feeling of liking something without intervention, while motivation is the drive to achieve success in something you like. In learning, to motivate students to achieve success, their interests need to be directed first. Where success in learning is measured based on the acquisition of learning outcomes. The strengths and weaknesses of student interest and motivation will influence learning outcomes. Based on this statement, it appears that there is a relationship between interest, motivation, and learning outcomes in teaching and learning activities. In this way, it was inspired to carry out research that aims to find out the correlation between interest, motivation, and learning outcomes which are seen based on differentiated learning with the research subject is students of X class in SMA Darussalam Blokagung Karangdoro Tegalsari Banyuwangi who were randomly selected. The kind of research correlation with the data collection method used was questionnaires and documentation and the data analysis method, namely SEM PLS. Based on the research results, it appears that there is a correlation between interest, motivation, and learning outcomes through differentiated learning. Keywords: interest, motivation, learning outcomes, and learning, differentiate